Surge history of Múlajökull, Iceland, since 1945 detected with remote sensing data - Magnús Freyr Sigurkarlsson 1990- (2015)
Remote data since 1945 to 2014 was gathered through free open source data bases for the purpose to map and measure surges of the Múlajökull outlet glacier at the Hofsjökull ice cap in central Iceland. Average surge size and frequency since 1945 is measured and calculated by mapping and comparing glacier margins and moraines from various years. Surging happens on average once every 10 years with the average extension of 150-300 m and affects an area of 0.4-1.3 km2 of the forefield. Múlajökull has retreated rapidly since 1995 with the largest continuous retreat during 1992-2008 of about 600 m and has not been smaller for at least 70 years. Retreat rate of 30-40 m/a remains similar throughout the period, and indicates that negative mass balance of Hofsjökull is the main reason for successively smaller surges and continuous glacier retreat in the past 20-30 years. Due to smaller and less extensive surges, older moraines are preserved in the forefield and can therefore be used to reconstruct former ice-margins and surge limits. Comparison between remote sensing and end-moraine mapping in this study and ground measurements by the Icelandic Glaciological Society (IGS) suggests that at least 6 surges have taken place since 1945. This comparison also shows a significant difference between the two methods. The difference is caused by a residual error of ±15 m deriving from the difficulties with registering and distributing ground control points for georeferencing of aerial photographs. Further actions towards registration of aerial photographs and correlation between ground measurements and remote sensing measurements is needed to achieve better comparison for these two methods. Markmið rannsóknarinnar var að kortleggja og mæla framhlaup í Múlajökli, sem er framhlaupsjökull í sunnanverðum Hofsjökli. Út frá loftmyndum og gervitunglamyndum frá 1945 til 2014 voru jökuljaðar og jökulgarðar Múlajökuls kortlagðir og bornir saman til að meta lengd og stærð framhlaupa sem verða að jafnaði á 10 ára fresti. Við meðal-framhlaup ...